Applying critical discourse analysis to classrooms. Issue 2 (2nd April 2020) - Jenks, Christopher J.
ABSTRACT: This special issue provides a collection of cutting-edge and state-of-the-art research that examines the wider sociocultural and sociopolitical aspects of classroom discourse. The current issue is the journal's first attempt to collectively explore what can be captured when looking at classroom discourse through a critical lens. The contributors of the special issue draw from theoretical perspectives that typify the diversity that exists in critical approaches to classroom discourse.